Análise de processos de escoamento de fluido nas escalas de poro e contínuo - Getirana Ramirez, Mateus (2022)
Understanding fluid flow processes in natural and industrial media is important for many industrial and environmental applications. For example, estimating fluid flow processes during oil and gas production is essential to enhance oil recovery. However, fluid flow may be different depending on several conditions such as properties of the fluid itself, and of the medium in which it flows. Considering the different scenarios that occur during petroleum exploration, the flow behavior was studied using computational models at two different times during the production process. One model refers to fluid flow in pipelines (the macro scale) subject to unconventional rheological characteristics, known as non-Newtonian fluids, for which simulators capable of predicting their behavior were developed using a more compact formulation that is less empirical. The second model refers to the digital evaluation of a porous medium at a micro scale (the pore network at the plug/core level) using statistical parameters to characterize the impact of pore-scale changes on the fluid flow properties